Optimizing the Application of Surgery for Degenerative Cervical Myelopathy [AO Spine RECODE-DCM Research Priority Number 10]. Issue 1 (February 2022) - Rodrigues-Pinto, Ricardo; Montenegro, Thiago S.; Davies, Benjamin M.; Kato, So; Kawaguchi, Yoshiharu; Ito, Manabu; Zileli, Mehmet; Kwon, Brian K.; Fehlings, Michael G.; Koljonen, Paul A.; Kurpad, Shekar N.; Guest, James D.; et al.
Study Design: Literature Review (Narrative). Objective: To introduce the number 10 research priority for Degenerative Cervical Myelopathy: Individualizing Surgery. Methods: This article summarizes the current recommendations and indications for surgery, including how known prognostic factors such as injury time, age, disease severity, and associated comorbidities impact surgical outcome. It also considers key areas of uncertainty that should be the focus of future research. Results: While a small proportion of conservatively managed patients may remain stable, the majority will deteriorate over time. To date, surgical decompression is the mainstay of treatment, able to halt disease progression and improve neurologic function and quality of life for most patients. Whilst this recognition has led to recommendations on when to offer surgery, there remain many uncertainties including the type of surgery, or timing in milder and/or asymptomatic cases. Their clarification has the potential to transform outcomes, by ensuring surgery offers each individual its maximum benefit. Conclusion: Developing the evidence to better guide surgical decision-making at the individual patient level is a research priority for Degenerative Cervical Myelopathy.